(3GdYhGed GdeGFI aj GdfMhs - (3YHO GdbGgQ Hf YHO GdQMef Hf eMeO GdLQLGfj, CHh HcQ,J (B471 (3g` s ((3CMeO Hf YKeGf s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf , hGdUdGI hGdSdGe Ydi eMeO hBdg hUMHg CLeYjf , hHYO aEf GdYhGed ai GdfMh Ydi eG Cdag GdTjN GdEeGe YHO GdbGgQ Hf YHO GdQMef GdLQLGfi QMeg Gddg Ydjg eGFI YGed , hgj JfbSe bSejf daXjI heYfhjI s
(3BNQgG (B:s
(3agPg eGFI YGed dG jSJZfi GdUZjQ hGdcHjQ hGdQajY Yf eYQaJgG hESJYeGdgG JeJ HYhf Gddg JYGdi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B310 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B606s
Keywords: (3GdfMhs